Digital marketing on total net sales of a livestock sector trading company (Research, Society and Development, 2025)
Digital marketing can have a significant impact on a company's sales by enabling it to reach its audience more effectively, build strong relationships with customers, and increase brand visibility. The goal of this research was to achieve an increase in net sales for a commercial company in the livestock sector with the help of digital marketing. The evaluation focused on the impact of the digital tactics used and their correlation with annual sales percentages, focusing on specific animal supplementation products. Various key metrics were examined, such as online visibility and social media engagement, highlighting the successful aspects of the strategy and identifying the most effective campaigns and digital channels. Additionally, potential areas for improvement were identified, with specific recommendations for optimizing online presence. Implementing social media in businesses is an advantage for strengthening the brand and market positioning. It is a simple tool to adapt to any entrepreneurial medium. An analysis of sales percentages was conducted alongside the Instagram channel, detailing the reach of different products and comparing it with the sales points on an annual basis. The work provided a comprehensive evaluation of digital marketing in the context of animal supplementation, highlighting both achievements and opportunities for improvement, and establishing connections with monthly sales results.